2015
DOI: 10.1989/ejihpe.v5i2.116
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional social support in elderly objective and subjective health ratings

Abstract: This paper aims to investigate the causes that explain the discrepancies between the effects of social relationships on health and wellness of the elderly people. Several disciplines of health sciences have developed different theories to explain the evidence that confirm the positive effects of social relations. Furthermore, there is acumuative evidence confirming most of the predictions der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Another study conducted in older adults suggested that having few social support networks could be a risk factor for reduced physical functioning, which was linked to dependence in at least one of the ADLs and instrumental ADLs ( 39 ). However, other studies have reported that supportive behaviors do not have a positive effect on well-being ( 40 ) or may even be detrimental to the recipient ( 41 ) or the provider ( 42 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted in older adults suggested that having few social support networks could be a risk factor for reduced physical functioning, which was linked to dependence in at least one of the ADLs and instrumental ADLs ( 39 ). However, other studies have reported that supportive behaviors do not have a positive effect on well-being ( 40 ) or may even be detrimental to the recipient ( 41 ) or the provider ( 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…2022.1028342 to dependence in at least one of the ADLs and instrumental ADLs (39). However, other studies have reported that supportive behaviors do not have a positive effect on well-being (40) or may even be detrimental to the recipient (41) or the provider (42).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, social support could also have a negative impact as a significant source of stress as feelings of indebtedness or guilt can occur 27 31. It is noteworthy that specific dimensions of supportive function referring to both quantitative and qualitative aspects depict beneficial roles on health being a personal resource in various stressful life events 31. Veiel pointed out that the types of available support should be included in a social support assessment 32.…”
Section: Introductionmentioning
confidence: 99%
“…Social support could also negatively impacts as a significant source of stress for unhealthy behaviours such as feeling of indebtedness or guilt to the support receivers 27 31. It is noteworthy that specific dimensions of supportive function referring to both of quantitative and qualitative aspects depict beneficial roles on health as personal resources in different stress life events 31. Veiel pointed out that types of available support should be included in the social support assessment 32.…”
Section: Introductionmentioning
confidence: 99%